Endoscopy in the Diagnosis of Small Intestine Diseases - Matsui, Toshiyuki; Matsumoto, Takayuki; Aoyagi, Kunihiko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
The purpose of this book is to improve diagnostic yields of capsule endoscopy and double-balloon endoscopy, because those procedures can depict nonspecific findings that may not lead to a proper diagnosis. Another reason for the publication was recognition of the difficulty in distinguishing enteroscopic findings of ulcerative colitis from those of Crohn$1 (Bs disease. From a practical point of view, it is important to observe endoscopic pictures first, then to compare the images of other modalities, and finally to compare macroscopic pictures of resected specimens. For that reason, a large number of well-depicted examples of small intestinal lesions were assembled to clarify differences among small intestinal lesions that appear to exhibit similar findings and morphologies. Comparisons with radiographic findings comprise another important element in diagnosis. There are limitations in endoscopic observations of gross lesions of the small intestine, with its many convolutions. In Japan, many institutions still practice double-contrast imaging, which provides beautiful results. Because a single disorder may exhibit variations, this volume includes multiple depictions of the same disorders. Also included are lesions in active and inactive phases, as both appearances are highly likely to be encountered simultaneously in clinical practice. The number of illustrated findings therefore has been limited to strictly selected cases.s
Part 1. General Considerations -- Chapter 1. Diagnostic Process for Small Intestinal Disease -- Chapter 2. Small Intestinal Radiography -- Chapter 3. Capsule Endoscopy -- Chapter 4. Double-Balloon Endoscopy -- Part 2. Specific Findings of Small Intestinal Lesions -- Chapter 5. Protruded Lesions -- Chapter 6. Submucosal Elevations -- Chapter 7. Ulcerative Lesions -- Chapter 8. Aphthous Lesions -- Chapter 9. Stenotic Lesions -- Chapter 10. Hemorrhagic Lesions -- Chapter 11. Diffuse Lesions -- Chapter 12. Reddish Lesions -- Chapter 13. Edematous Lesions -- Chapter 14. Case presentations: Flat / Small protrusions -- Chapter 15. Case Presentations: Depressions -- Chapter 16. Case Presentations: Protrusions of Submucosal Elevations -- Chapter 17. Case presentations: Protrusion with Ulcer -- Chapter 18. Case Presentations: Multiple Protrusions -- Chapter 19. Case Presentations: Ulcers -- Chapter 20. Case Presentations: Stenosis -- Chapter 21. Hemorrhagic Lesions -- Chapter 22. Reddened Lesions -- Chapter 23. Edematous Lesions -- Chapter 24. Erosive Lesions -- Chapter 25. Diffuse Granular or Diffuse Coarse Mucosal Lesions -- Chapter 26. Whitish Multi-Nodular Lesions -- Chapter 27. Intraluminal Growth -- Part 3. Basic Knowledge and Classification -- Chapter 28. On Tumors -- Chapter 29. On Inflammation.
Keywords: Medicine; Internal medicine; Gastroenterology; Oncology; Medicine & Public Health; Gastroenterology; Internal Medicine; Oncology